Basic Units: An Architectural Proposal for the Immigration Emergency in México - Sindy Melissa Godínez De León; Ruth María Garza de la Garza; Aíxa Carolina Becerra Vázquez (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The present study analyzes the reuse of basic emergency shelter units, intending to adapt them as temporary shelters for deported migrants on the border between México and the United States. In the current geopolitical context, characterized by restrictive immigration policies and increased mass deportations, it is essential to provide efficient and sustainable housing solutions. The methodology used is based on a typological, functional, and structural analysis of different models of temporary shelters, evaluating their viability, adaptability, durability, thermal efficiency, and sustainability are considered, as well as integrating design strategies that improve habitability conditions. The results show that existing basic units can serve as shelters with minimal modifications, incorporating renewable energy systems, thermal insulation, and optimized space distribution. The research highlights the role of architecture as a key tool in responding to migration crises, promoting innovative and resilient solutions, and addressing the growing need for humanitarian infrastructure on the border.